Bisphenol A Induces Hepatotoxicity through Oxidative Stress in Rat Model. (24th July 2012) - Hassan, Zeinab K.; Elobeid, Mai A.; Virk, Promy; Omer, Sawsan A.; ElAmin, Maha; Daghestani, Maha H.; AlOlayan, Ebtisam M.
Abstract : Reactive oxygen species (ROS) are cytotoxic agents that lead to significant oxidative damage. Bisphenol A (BPA) is a contaminant with increasing exposure to it and exerts both toxic and estrogenic effects on mammalian cells. Due to limited information concerning the effect of BPA on liver, this study investigates whether BPA causes hepatotoxicity by induction of oxidative stress in liver. Rats were divided into five groups: The first four groups, BPA (0.1, 1, 10, 50 mg/kg/day) were administrated orally to rats for four weeks. The fifth group was taken water with vehicle. The final body weights in the 0.1 mg group showed a significant decrease compared to control group. Significant decreased levels of reduced glutathione, superoxide dismutase, glutathione peroxidase, glutathione-S-transferase, glutathione reductase and catalase activity were found in the 50 mg BPA group compared to control groups. High dose of BPA (50 mg/kg) significantly increased the biochemical levels of ALT, ALP and total bilirubin. BPA effect on the activity of antioxidant genes was confirmed by real time PCR in which the expression levels of these genes in liver tissue were significantly decrease compared to control. Data from this study demonstrate that BPA generate ROS and reduce the antioxidant gene expression that causes hepatotoxicity.